Kerangka Terintegrasi Pareto–FMEA–FTA untuk Pengendalian Kualitas Berbasis Risiko pada Pemesinan Komponen Presisi: Studi Kasus Manufaktur Spinning Spinnerette - Alya Rahma Putri; Supriyati; Fibi Eko Putra (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2026)
This study aims to identify the dominant defect types, analyze potential failure modes and their associated Risk Priority Numbers, determine the root causes of primary failures, and formulate corrective action recommendations for the machining process of spinning spinnerette products at PT XYZ, Cikarang, Indonesia. A mixed-methods approach was employed, integrating Pareto Chart analysis, Failure Mode and Effect Analysis (FMEA), and Fault Tree Analysis (FTA) sequentially. Data were collected through field observation, structured interviews, FMEA questionnaires, and company documentation covering the period January–December 2025. Pareto Chart analysis revealed that rough surface defects (37.50%), non-conforming hole diameter (25.00%), and clogged holes (20.00%) collectively accounted for 82.50% of total recorded defects. FMEA yielded the highest Risk Priority Number for the rough surface failure mode (RPN = 240), while micro-crack defects recorded the highest Severity rating (S = 9), with an estimated financial loss of IDR 50,000,000.00 per unit. FTA identified that rough surface defects originate from the interaction of four primary factors: cutting tool condition, process parameters, operator competency, and production environment control. The 5W+1H-based corrective recommendations formulated in this study have the potential to reduce financial losses by up to IDR 476,000,000.00 annually and may be adopted as a risk-based quality control model applicable to analogous precision component manufacturing industries.